The Influence of Achievement Needs and Employee Competencies on Career Achievement - Wibisono, Galih; Hanif Mauludin (Yayasan Widyantara Nawasena Raharja, 2025)
This study examines the influence of achievement needs on career achievement and investigates the mediating role of employee competence among staff members of the Class I Correctional Institution in Malang. Employing an explanatory quantitative design, data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings reveal that the need for achievement has a positive and significant effect on both employee competence and career achievement. Furthermore, employee competence exerts a significant positive influence on career achievement and mediates the relationship between achievement needs and career outcomes. These results indicate that employees’ intrinsic drive to excel not only enhances their career achievement directly but also indirectly through competence improvement. Theoretically, this study contributes to the extension of McClelland’s Achievement Motivation Theory by demonstrating its applicability in a high-stress, bureaucratic public organization such as a correctional institution. Practically, the findings highlight the importance of developing programs that simultaneously foster achievement motivation and enhance competencies through training, recognition, and structured career pathways. Strengthening these aspects can improve both individual career advancement and organizational performance within correctional settings.